A Wohlfahrtiimonas chitiniclastica with a novel type of blaVEB–1-carrying plasmid isolated from a zebra in China - Guan, Jiayao; Zhou, Wei; Guo, Jingyi; Zheng, Lin; Lu, Gejin; Hua, Fuyou; Liu, Mingwei; Ji, Xue; Sun, Yang; Zhu, Lingwei; Guo, Xuejun (Frontiers in Microbiology, 2023)
Background Wohlfahrtiimonas chitiniclastica is an emerging fly-borne zoonotic pathogen, which causes infections in immunocompromised patients and some animals. Herein, we reported a W. chitiniclastica BM-Y from a dead zebra in China. Methods The complete genome sequencing of BM-Y showed that this isolate carried one chromosome and one novel type of blaVEB–1-carrying plasmid. Detailed genetic dissection was applied to this plasmid to display the genetic environment of blaVEB–1. Results Three novel insertion sequence (IS) elements, namely ISWoch1, ISWoch2, and ISWoch3, were found in this plasmid. aadB, aacA1, and gcuG were located downstream of blaVEB–1, composing a gene cassette array blaVEB–1–aadB–aacA1–gcuG bracketed by an intact ISWoch1 and a truncated one, which was named the blaVEB–1 region. The 5′-RACE experiments revealed that the transcription start site of the blaVEB–1 region was located in the intact ISWoch1 and this IS provided a strong promoter for the blaVEB–1 region. Conclusion The spread of the blaVEB–1-carrying plasmid might enhance the ability of W. chitiniclastica to survive under drug selection pressure and aggravate the difficulty in treating infections caused by blaVEB–1-carrying W. chitiniclastica. To the best of our knowledge, this is the first report of the genetic characterization of a novel blaVEB–1-carrying plasmid with new ISs from W. chitiniclastica.